(untitled) (Eurasian Journal of Media and Communications, 2024)
Artificial Intelligence (AI) is increasingly being utilized to enhance Public Relations (PR) practices and improve communication efforts in industries and other sectors. This paper examined the knowledge and application of artificial intelligence in public relations practice within the Agip Oil and Gas industry. Four objectives were formulated for the study. Some of the objectives were to examine the extent to which AI tools such as natural language processing, sentiment analysis, chatbots, content generation tools, predictive analytics, and media monitoring tools, are known and employed in PR activities at Agip Oil and Gas. From the objectives, four research questions were also raised to guide the study. The design used for the study is survey. Interview was the instrument for data collection. Qualitative analysis was adopted to analyze the data gathered. The findings reveal that Agip Oil and Gas is aware of the potential of AI in PR. The researchers also found out that the industry have invested heavily in acquiring some of the AI tools. Key areas of knowledge and application include sentiment analysis for customer feedback analysis and media monitoring tools for tracking public perception and trends. One of the recommendations in this paper is that an in-depth study on the perception and utilization of AI in public relation practices among professionals should be carried out in Agip oil and gas industry.